Prolegomena to any future metaphysics that will be able to come forward as science : with selections from the Critique of pure reason - Kant, Immanuel, 1724-1804; Hatfield, Gary C. (Gary Carl); Kant, Immanuel, 1724-1804. (Cambridge : Cambridge University Press, 2004)
Kant is the central figure of modern philosophy. He sought to rebuild philosophy from the ground up, and he succeeded in permanently changing its problems and methods. This revised edition of the Prolegomena, which is the best introduction to the theoretical side of his philosophy, presents his thought clearly by paying careful attention to his original language. Also included are selections from the Critique of Pure Reason, which fill out and explicate some of Kant's central arguments (including famous sections of the Schematism and Analogies), and in which Kant himself explains his special terminology. The first reviews of the Critique, to which Kant responded in the Prolegomena, are included in this revised edition. The volume is completed by a historical and philosophical introduction, explanatory notes, a chronology, and a guide to further reading.
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: elektronické knihy; electronic books; Knowledge, Theory of; Metaphysics